A scanning electron microscopy study of root surface smear layer removal after topical application of EDTA plus a detergent - Sampaio, José Eduardo Cezar [UNESP]; Campos, Flávia Pavan [UNESP]; Pilatti, Gibson Luiz [UNESP]; Theodoro, Letícia Helena [UNESP]; Leite, Fábio Renato Manzolli [UNESP] (Faculdade De Odontologia De Bauru - USP, 2005)
The aim of the present study was to compare root surface smear layer removal following topical application of EDTA and EDTA-T (Texapon). Extracted human teeth had their cementum removed and were mechanically scaled. A total of 220 root specimens were obtained and were randomly assigned to the following groups: I-saline solution (control), II-EDTA; III-EDTA-T. Groups II and III specimens were assigned to different EDTA gel concentrations: 5%, 10%, 15%, 20% and 24%. Smear layer removal score was assessed for each specimen by scanning electron microscopy. The results demonstrated that EDTA and EDTA-T gel led to a higher root surface smear layer removal when compared to the control group. The 5% EDTA gel also showed a higher smear layer removal than the 15%, 20% and 24% EDTA gels (p<0.05). No difference could be found between the different concentrations of EDTA-T gels tested (p>0.05). EDTA gels had statistically significantly lower smear layer scores than the EDTA-T gels for the 5% and 10% concentrations. The results suggested that topical application of EDTA or EDTA-T gel led to significant smear layer removal of the mechanically treated root surfaces. The addition of a detergent to the EDTA gel formula did not improve smear layer removal of the root surface.

O objetivo do presente estudo foi comparar, através de microscopia eletrônica de varredura, a remoção de smear layer de superfícies radiculares após aplicação tópica de gel de EDTA com gel de EDTA-T (Texapon). Foram utilizados dentes humanos que foram submetidos a remoção de cemento radicular e raspagem. As amostras dos dentes foram divididas em 3 grupos: Grupo I- (controle) (n=20); Grupo II- gel de EDTA (pH 7,0) nas concentrações de 5%,10%,15%,20% e 24% (n=100); Grupo II -gel de EDTA-T (pH 7,0) nas concentrações acima descritas (n=100). As fotomicrografias foram avaliadas através de um índice e os dados foram estatisticamente analisados. Ambos os tratamentos com EDTA foram efetivos na remoção de smear layer quando comparados ao grupo controle. O gel de EDTA a 5% demonstrou maior capacidade na remoção de smear layer quando comparado com as concentrações de 15%, 20% e 24% (p<0,05). Não houve diferença entre as concentrações de géis de EDTA-T (p>0,05). Os géis de EDTA foram mais efetivos que o EDTA-T nas concentrações de 5 e 10%. Os resultados sugerem que a aplicação tópica de EDTA ou EDTA-T é efetiva na remoção de smear layer, principamente em baixas concentrações e a adição do Texapon não promove vantagens neste tratamento.
Remoção de smear layer de superfícies radiculares com aplicação tópica de EDTA com detergente. Análise em microscopia eletrônica de varredura
Keywords: Periodontal disease; EDTA etching; Smear layer; Root planing; Doença periodontal; EDTA, condicionamento; Smear layer; Raspagem